The Influence of Oil Concentration, Nitrogen and Phosphorus Composition on Crude Oil Biodegradation by Epyzim and Mixed Cultures of Pseudomonas aeruginosa and Arthrobacter simplex - ERLIZA NOOR; LINAWATI HARDJITO (Indonesian Society for microbiology, 2008)
Biological methods have gained attention as an alternative treatment for oil degradation in pollution remediation. External and internal factors have a great influence on crude oil biodegradation. This experiment studied the effect of oil concentrations and ratios of Ammonium and Phosphate on oil degradation in mixed cultures of local strains of Pseudomonas aeruginosa and Arthrobacter simplex. The oil degradation ability of this mixed culture was compared to the dormant culture of Epyzim. The increase of oil concentration, from 1, 3, 5 and 10% (w/v), significantly lowered the ability of both cultures to degrade the oil i.e from 83 % for 1% oil concentration to 64% for 10% oil concentration using local strains. The local strains showed better capability compare to the dormant culture. Medium composition was designed by three levels of ammonium concentration (7.6, 37.9 and 75.8 mg l-1) and two levels of phosphate concentration (2.0 and 9.9 mg l-1). The ratio of ammonium to phosphate of 3.8:1.0 in the growth media has resulted the maximum level of oil degradation, i.e 83% and 88%, for dormant and local cultures respectively. The results suggest a potential usage of local microorganisms in degrading crude oil-polluted water.